The Rise of Market-Capitalism and the Roots of Anti-American Terrorism - Daniel Meierrieks; Tim Krieger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This contribution examines the role of market-capitalism in anti-American terrorism. It differentiates between level- and rate-of-change-effects associated with market-capitalist development and their respective relationship with anti-U.S. violence. While this contribution argues that higher levels of capitalist development consistent with the capitalist-peace literature coincide with less anti-American terrorism, it also suggests that the process of marketization has inflammatory effects on anti-American terrorism. Using panel data for 149 countries between 1970 and 2007, this contribution indeed finds support for these two hypotheses. The findings are further corroborated by system-level time-series evidence. Considering the findings, it is argued that a higher level of market-capitalism is associated with less anti-American terrorism by creating economic interdependencies and a convergence of pro-peace values and institutions. The destabilizing effects of the marketization process are argued to stem from the violent opposition of various anti-market interest groups to economic, politico-institutional and cultural change initiated by a transition towards a market economy. These interest groups deliberately target the U.S. as the main proponent of modern capitalism, globalization and modernity, where anti-American terrorism serves the purpose of consolidating their respective societal position by means of voicing dissent, rolling back pro-market reforms and limiting the perceived Americanization of their communities. The findings of this contribution suggest that the U.S. may ultimately become a less likely target of transnational terrorism through the establishment of market economies, but should not disregard the disruptive political, economic and cultural effects of the marketization process in non-capitalist societies.
Keywords: D74; O10; P10; 330